2016
DOI: 10.1111/liv.13102
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of sofosbuvir‐containing regimens in hepatitis C‐infected patients with impaired renal function

Abstract: Sustained viral clearance was achieved in 83% of patients with renal impairment (eGFR ≤45 ml/min/1.73 m(2) ) treated with SOF-containing regimens. However, these patients had higher rates of anaemia, worsening renal dysfunction and serious adverse events regardless of use of RBV. Patient with renal impairment require close monitoring and should be treated by providers extensively experienced with SOF-containing regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
237
5
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(272 citation statements)
references
References 18 publications
17
237
5
13
Order By: Relevance
“…This study included traditionally difficult to treat patients, with 43% being previously treated nonresponders and 52% being either transplant recipients or having decompensated cirrhosis. The SVR rate in this study compares favorably to those reported in other studies, which vary widely from 67% to 100%16, 17, 18, 19, 20, 21, 22, 23 (Table 2). Several aspects of these other studies may have contributed to reduced SVR rates, including the use of reduced‐dose SOF18, 19, 20 and the use of regimens with less potential to achieve SVR, such as SOF/RBV and SOF/pegylated interferon/RBV 16, 17…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This study included traditionally difficult to treat patients, with 43% being previously treated nonresponders and 52% being either transplant recipients or having decompensated cirrhosis. The SVR rate in this study compares favorably to those reported in other studies, which vary widely from 67% to 100%16, 17, 18, 19, 20, 21, 22, 23 (Table 2). Several aspects of these other studies may have contributed to reduced SVR rates, including the use of reduced‐dose SOF18, 19, 20 and the use of regimens with less potential to achieve SVR, such as SOF/RBV and SOF/pegylated interferon/RBV 16, 17…”
Section: Discussionsupporting
confidence: 83%
“…It is worth noting that worsening renal function has been reported in subjects receiving SOF‐based regimens who have moderate renal impairment16 or have undergone kidney transplant 24. Because no control was available for these studies, it is difficult to attribute the worsening renal function to SOF exposure versus natural progression of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, few small open-label treatment studies (one of them by our group) using Simeprevir and full dose or dose-adjusted Sofosbuvir in patients with advanced CKD and ESRD did not demonstrate significant AEs while achieving high rates of SVR12 (8)(9)(10)15). However, until further studies with larger numbers of patients are available, Sofosbuvir based regimens are not recommended for HCV treatment in the CKD stage 4-5 setting.…”
mentioning
confidence: 99%
“…DAA regimens that require ribavirin have posed a particular concern due to poor tolerance of ribavirin in patients with advanced renal disease. Despite these limitations, a number of groups had reported smaller case series of successful treatment with interferon or DAAs with or without ribavirin (8)(9)(10). Fortunately, this situation has evolved in a more favorable way as studies like C-SURFER and RUBY demonstrated safety and efficacy of newer DAAs in the CKD stage 4-5 and dialysis setting (11,12).…”
mentioning
confidence: 99%
“…DAA regimens approved for renal patients SOF-based regimens are registered for treatment of renal patients with >30 ml creatinine/min × 1.73 mq body surface. This notwithstanding, data collected by the observational study TARGET indicates that 88% of 15 US patients with stage 4 or 5 kidney impairment were able to achieve an SVR in the face of an increased rate of adverse events and transient deterioration of renal function [8]. In that study, the SVR rate in 1495 patients with >45 IU/ml eGFR receiving SOF-based regimens were similar to that of 64 patients with <45 IU/ml eGFR, again with an increased rate of adverse events in patients with more deteriorated renal function.…”
mentioning
confidence: 99%